Analisis Pengendalian Persediaan Bahan Baku Parfume Menggunakan Metode Min-Max - Ramayani, Ramayani (Journal Global Technology Computer, 2023)
A perfume business where raw material supplies are the most important element in the production carried out by the business owner. Inventory can be defined as materials stored for use in the future. Inventory is one of the issues that needs to be considered in relation to production process activities. However, the quantity of inventory should not be too large so that the capital invested in inventory and the costs it causes are not too large and also not too small because it can slow down the production process. Therefore, it is necessary to plan and control raw materials. Consideration of the importance of the availability of raw materials according to the production quantity means that these raw materials must always be ready in the same quantity each production period so that the supply of these raw materials is always met at a minimum cost. The raw material inventory control method used in this research is the min-max stock method. The min-max stock method is a raw material control method which is based on the assumption that raw material inventory is at two levels, namely the maximum level and the minimum level. If the maximum level and minimum level have been set, then when the inventory reaches the minimum level an order for raw materials must be made to place the inventory at the maximum level.